2019
DOI: 10.1021/acs.chemrev.9b00230
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation over Supported Metal Catalysts: From Nanoparticles to Single Atoms

Abstract: Selective catalytic hydrogenation has wide applications in both petrochemical and fine chemical industries, however, it remains challenging when two or multiple functional groups coexist in the substrate. To tackle this challenge, the “active site isolation” strategy has been proved effective, and various approaches to the site isolation have been developed. In this review, we have summarized these approaches, including adsorption/grafting of N/S-containing organic molecules on the metal surface, partial cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
853
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 1,120 publications
(866 citation statements)
references
References 343 publications
7
853
0
6
Order By: Relevance
“…Gold is among the least active metals toward molecules at a solid–liquid or solid–gas interface. For example, it has the highest energy barrier for the dissociation of H 2 and the least stable chemisorption state 1 3 . This inertness has been attributed to the full filling of the antibonding d state on adsorption and the small orbital overlap with the adsorbate according to the d -band model 1 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Gold is among the least active metals toward molecules at a solid–liquid or solid–gas interface. For example, it has the highest energy barrier for the dissociation of H 2 and the least stable chemisorption state 1 3 . This inertness has been attributed to the full filling of the antibonding d state on adsorption and the small orbital overlap with the adsorbate according to the d -band model 1 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…I n recent years, single-atom catalysts (SACs) have attracted considerable attention as a means by which to maximize precious metal utilization and generate well-defined, uniform active sites [1][2][3][4][5][6][7][8][9] . SACs exhibit superior catalytic performance (activity and/or selectivity) for thermal oxidation 1,10-12 and hydrogenation 9,[13][14][15][16][17] , electrochemistry [18][19][20][21][22][23] , and industrially important processes such as the water-gas shift reaction, C-C coupling, C-H activation, and methanol reforming 11,[24][25][26][27] . Counter-intuitively, SACs were recently reported to exhibit better stability than their nanoparticle (NP) counterparts, highlighting their potential for commercial applications 28,29 .…”
mentioning
confidence: 99%
“…It has been known that as the homolytic dissociation of H 2 normally requires the denotation of d-electrons of metal to H 2 , and therefore a high electron density of the Ru sites is beneficial for the H dissociation. [59] The dissociated hydrogen atoms could diffuse into the adjacent unsaturated Co sites and facilitate hydrogenation reaction. It has been reported that the selective hydrogenation of C=C bonds could be improved by the metalÀ support/promoter interaction to modulate the electronic properties of metal active site.…”
Section: Identification Of Active Sites For Ae Hydrogenation Via Dftmentioning
confidence: 99%